Identification Of Core Indicators Of The Dynamic Efficiency Evaluation Method Of Design Solutions - Semenov, Aleksandr Sergeevich; Kuznetsov, Vladimir Sergeevich (Archives of Business Research, 2017)
Optimization methods in mining industry, taking into account the time factor develop abroad from the end of 19 century. However, in the context of policy centrally planned economy development of dynamic methods substantially restrained. In the last decade have developed research in the field of dynamic methods for solving design problems of the domestic mining industry, including a number of official recommendations [1, 2]. However, the formation of a national market economy, especially the contemporary stage of the open mining (particularly complex), the development of mineral resources markets require constant adjustment and improvement of dynamic design techniques of quarries. In the mining industry specific investments, establishing the capital investment is several times bigger than the in manufacturing industries. Dynamic evaluation methods taking into account the time factor can help you determine the value of the investment in time unlike the way economic evaluation methods. Mineral markets there is a tendency for problems with the deterioration of the of economic indicators of development. This is due to the oxygen dissipated rich deposits, increasing depth development, involvement in the development of minerals with lower quality involved and content of useful components, to be found in the more difficult geological and location conditions. Investment opportunities of the development mineral-raw materials base have significant limitations, the result of which is a disproportion between the mining, metallurgical or processing capacity.